2016
DOI: 10.1515/ms-2016-0229
|View full text |Cite
|
Sign up to set email alerts
|

Pseudo-amenability and pseudo-contractibility for certain products of Banach algebras

Abstract: Let A and B be two Banach algebras and let θ be a nonzero character on B. In this paper, we deal with the θ-Lau product A × θ B that was first introduced by A. T. Lau for certain Banach algebras known as Lau algebras and recently by M. S. Monfared for all Banach algebras; we study pseudo-amenability, pseudo-contractibility and character pseudo-amenability of A × θ B and their relations with A and B.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Recently, Ghaderi et al in [8] studied pseudo-contractibility of θ-Lau product of Banach algebras. First, we give a simpler proof of [8,…”
Section: Pseudo-contractibility Of θ-Lau Product Of Banach Algebrasmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Ghaderi et al in [8] studied pseudo-contractibility of θ-Lau product of Banach algebras. First, we give a simpler proof of [8,…”
Section: Pseudo-contractibility Of θ-Lau Product Of Banach Algebrasmentioning
confidence: 99%
“…In Section 4, we characterize pseudo-contractibility of θ-Lau product of Banach algebras. In [8], the authors addressed an open question whether or not A × θ B is pseudo-contractible if A is contractible and B is pseudo-contractible. Here, we give an affirmative answer to this question.…”
Section: Introductionmentioning
confidence: 99%
“…In the Section 3 we focus on pseudo-amenability of A × θ B. Pseudo-amenability of A × θ B was studied by E. Ghaderi et al [10]. They showed that pseudo-amenability of A × θ B implies pseudo-amenability of B, and implies pseudo-amenability of A whenever A has a bounded approximate identity.…”
Section: Introductionmentioning
confidence: 99%
“…was studied by E. Ghaderi et al in [10]. They prove that pseudo-amenability of A × θ B implies pseudo-amenability of B, and implies pseudo-amenability of A whenever A has a bounded approximate 2010 Mathematics Subject Classification.…”
Section: Introductionmentioning
confidence: 99%